Compact device for assessment of microorganism motility - Pomarico, Juan Antonio (2004)
We have designed and constructed a simple and reliable instrument, based on dynamic speckle interferometry, which allows the determination of the relative degree of motility for microorganisms. A measurement can be carried out in a few seconds and parasites have been used for test purposes. An ad hoc software was also developed showing easy operation characteristics. This instrument surpasses the purely qualitative methodology employed by human operators, that can be affected by great errors, fatigue, etc. Besides, it does not require using image formation systems (such as a microscope) and a frame grabber is not mandatory. © 2004 American Institute of Physics.